Perkembangan Sistem Pendidikan di Malaysia - Hadit Pratama; Mislaini Mislaini; Aidil Rahman (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This article examines the education system in Malaysia, focusing on key aspects such as the structure of education, curriculum, government policies, as well as the challenges and opportunities within the country's educational landscape. The research also highlights how technological advancements and social shifts impact the delivery of education. Additionally, this article will analyze a news example related to Malaysia's education system, with an emphasis on identifying spelling errors found within the text. These errors will be analyzed to enhance the understanding of the importance of using correct language, especially in media that addresses educational topics.